Knowledge, attitude and communication in relation to the goods and services tax compliance among wood product manufacturers in Peninsular Malaysia - Harun, Zubaidah (2016)
GST is a new indirect tax system replaced the Sales and Services Tax (SST) in Malaysia on April 1,2015.Therefore, this study is one of the first conducted on the wood product manufacturers in Peninsular Malaysia (PM). The aim of this study is to develop a model of GST compliance which is Knowledge, Attitude and Communication (KAC) model based on Knowledge, Attitude and Practice (KAP) model. There are five objectives to achieve this aim this study. Firstly, to measure the level of compliance, understanding of knowledge and attitude (cognitive and affective) toward GST. Secondly, to identify the most effective communication channel in acquiring and gaining an understanding of the GST knowledge. Thirdly, to determine the category of knowledge (concept, legal, technical and technology) that provides the most influence to the GST compliance among the wood products manufacturers. Fourthly, to examine the relationship between knowledge, attitude and communication channels toward GST compliance. Finally, is examining the moderation effect of the size of the company on the relationship between knowledge, attitude and communication channels toward GST compliance.The quantitative survey method was used on the selected respondents based on the propositional stratified sampling technique from 2,290 the GST-registered person. There are 352 (88%) questionnaires returned from the survey out of 400 respondents. Data were analysed using SPSS for descriptive results. The structural equation modelling (SEM) using AMOS was deployed for the regression analysis.The descriptive results revealed the level of GST compliance as moderate with a mean value of 6.22 in the range of 3.34 to 6.66.Similarly,understanding of GST knowledge shows a moderate level with the mean value of 5.77. The level of affective (perception) is more pronounce than the cognitive (intellectual) toward GST compliance with a mean value of 5.57 and 5.32 respectively. Consultation service from the tax consultant with a mean value of 6.76 was found to be the most effective communication in acquiring and gaining an understanding of the GST knowledge by the wood products manufacturers. Concept and technical knowledge served a significantly (p<0.001) high impact to the GST compliance with regression coefficient of 0.357 and 0.360 respectively. Whilst, knowledge and attitude constructs have a significant effect (p-value = 0.05) toward GST compliance. On the other hand, communication channels have insignificant effect. Prominently, the large companies provide moderation effect on the path of the relationship between knowledge and attitude toward GST compliance.Based on the results it reveals the level of the readiness and preparedness of the wood product manufacturers is at a satisfactory level in term of understanding and perception. Utilization of intellectual understanding of GST knowledge could raise the perception level among the wood product manufacturers in complying GST. The study supports the theory of the significant relationship between knowledge and attitude toward GST compliance. Similarly to the findings of previous studies, the large companies proved to provide the moderation effect on the correlation between knowledge and attitude toward GST compliance. Methodologically, the used of AMOS in this study has contributed to the latest addition to the literature of research method in the field of GST being the first to be used.The findings could be utilized by a variety of the stakeholders such as FDPM, MTIB and the wood-based associations i.e. KLFEA, MPMA, PEKA, MWIA, TEAM, MWMJC and MFC in developing GST education programs for their members with minimal cost by collaborating with RMCD. This could maximize the level of GST compliance by raising the level of understanding on GST knowledge and the same time forming a more positive attitude among the wood product manufacturers in PM as well as Sabah and Sarawak.